Phylogeny of the Alismatales (Monocotyledons) and the relationship of Acorus (Acorales?). (16th April 2015) - Petersen, Gitte; Seberg, Ole; Cuenca, Argelia; Stevenson, Dennis W.; Thadeo, Marcela; Davis, Jerrold I.; Graham, Sean; Ross, T. Gregory
Abstract: A phylogenetic analysis of the early branching lineages of the monocotyledons is performed using data from two plastid genes ( rbcL and matK ), five mitochondrial genes ( atp1, ccmB, cob, mttB and nad5 ) and morphology. The complete matrix includes 93 terminals representing Acorus, the 14 families currently recognized within Alismatales, and numerous lineages of monocotyledons and other angiosperms. Total evidence analysis results in an almost completely resolved strict consensus tree, but all data partitions, genomic as well as morphological, are incongruent. The effects of RNA editing and potentially processed paralogous sequences are explored and discussed. Despite a decrease in incongruence length differences after exclusion of edited sites, the major data partitions remain significantly incongruent. The 14 families of Alismatales are all found to be monophyletic, but Acorus is found to be included in Alismatales rather than being the sister group to all other monocotyledons. The placement is strongly supported by the mitochondrial data, atp1 in particular, but it cannot be explained as an artifact caused by patterns of editing or by sampling of processed paralogues.